THE EFFECT OF THE COVID 19 VIRUS AND ONLINE LEARNING ON ENGLISH SUBJECTS IN JUNIOR HIGH SCHOOL - Dhaniel Prasetyo Irianto; Arman Syah Putra; Nurul Aisyah; VH. Valentino; Matdio Siahaan (Bajang Institute, 2021)
The background of this research writing is to know what variables affect junior high school, and it can be seen that these variables have a significant effect or not, because they can affect many things in school kindness at school. The method used in writing this research is to use quantitative methods which will be surveyed to 100 people who are randomly selected so that they can find out the data directly in the field because with the appropriate data it will be able to produce good research and can be used as a basis for future research. The problem raised in this study is how the Corona virus variable and the online learning system can affect junior high schools that use English subjects as compulsory subjects in Junior High Schools. Can the Corona virus variable and online learning system variables affect schools Junior Intermediate. The purpose of this study will be to find out what variables can affect the teaching and learning system in junior high schools, in order to improve the learning and teaching system in the future so that they can find out the weaknesses and strengths of the learning system.